Urgensi Manajemen Transformasi Bagi Perseorang dan Institusi - Ardhinur Ardhinur; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2023)
Transformation is an absolute thing that cannot be avoided by anyone because transformation is certain and will occur. The policy of transformation itself such as: transformation in behavior, value systems, procedures, ways of working, facilities and infrastructure used, mindset, and behavior. Humans are also required to be able to adjust the situation to the transformation and the transformation policy itself. Change management is an activity that is oriented to make transformation in a person, institution and association of institutions (organizations) for the future in order to achieve something desired. The frame of mind used is a variety of empirical research.This variety of scientific writing is to solve problems by combining data, working on data, then analyzing and interpreting to subsequently get a conclusion. This writing is included in literature studies with the type of data collected in the form of research results from various articles, library sources and documents in accordance with the theme. With the results of transformation management is something that must be realized by a person or institution in order to improve the quality and quantity of a person or institution to be even better in the future. By minimizing or minimizing interference from outside and being able to adapt effectively and efficiently both inside and outside the environment. Without tarsnformation, a person or institution will not be able to survive